Cost of the typhoid conjugate vaccine introduction through an integrated campaign and follow-on routine immunization in Malawi - Frédéric Debellut; George Bello; Mike Chisema; Rouden Mkisi; Moses Kamzati; Clint Pecenka; Emmanuel Mugisha (Vaccine: X)
Malawi introduced typhoid conjugate vaccine (TCV) in 2023 through an integrated campaign delivering TCV alongside other vaccines and interventions (measles rubella vaccine (MRV), bivalent oral polio vaccine (OPV), and vitamin A Supplementation). The campaign sought to reach all children 9 months to younger than 14 years, representing more than 9 million individuals, and about half the country’s population. Following the campaign, TCV was incorporated into the routine immunization program for 9-month-old infants. We conducted a micro-costing study at 50 randomly selected health facilities, 10 districts, and at national level to retrospectively assess the financial and economic cost of the integrated campaign, as well as prospectively estimate the cost of delivering TCV in the routine immunization system. The financial and economic costs per dose for all interventions delivered in the campaign were $0.49 ($0.42;$0.57) and $0.84 ($0.67;$1.02), respectively. The main activities and cost types varied; human resources represented the main resource at health facility level, and per diem at district and national levels. The financial and economic cost to routinely deliver a dose of TCV were $0.44 ($0.17;$0.87), and $2.37 ($1.39;$3.53), respectively, with human resources as the main resource used by the routine program at all levels.The cost per dose delivered in the integrated campaign in Malawi was comparable with other integrated campaigns and was lower than the reported cost to deliver TCV in single antigen campaigns in India and Zimbabwe. Integrated campaigns may represent an opportunity to introduce new vaccines such as TCV to lower the cost per dose delivered. Attention should be given to challenges coming with integration, such as the burden for healthcare workers.Evidence produced by this study can be used in Malawi to inform financial sustainability of the TCV program and should inform decisions and strategies for implementation by other countries.